VD_FINDINFO Arrêt / 2013 / 107 vom 19. Februar 2013 - VD Tribunal cantonal (2013)
DÉLAI-CADRE, INDEMNITÉ JOURNALIÈRE, DROIT TRANSITOIRE | 27 al. 2 let. b LACI, 27 al. 2 let. c LACI, 8 al. 1 let. e LACI